Standard electroencephalography in clinical psychiatry : a practical handbook - Boutros, Nashaat N. (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
"This book provides a concise overview of the possible clinical applications of standard EEG in clinical psychiatry. It starts with a short history then describes the physiologic basis of the EEG signal. The material is clearly presented throughout, with figures, tables with summaries of relevant findings, flow diagrams for diagnostic work-up, boxes with learning points, and short lists of key references"--
"This book provides a concise overview of the possible clinical applications of standard EEG in clinical psychiatry"--
Front Matter -- Historical Review of Electroencephalography in Psychiatry / Nash Boutros -- Physiologic Basis of the EEG Signal / Paola Bucci, Silvana Galderisi -- EEG Recording and Analysis / Oliver Pogarell -- Normal EEG Patterns and Waveforms / Paola Bucci, Armida Mucci, Silvana Galderisi -- Abnormal Patterns / Oliver Pogarell -- The Role of EEG in the Diagnostic Work up in Psychiatry: Nonconvulsive Status Epilepticus, Frontal Lobe Seizures, Non-Epileptic Seizures / Silvana Riggio -- EEG in Childhood Psychiatric Disorders / Mary W Roberts, Nash Boutros -- EEG in Psychoses, Mood Disorders and Catatonia / Nash Boutros, Silvana Galderisi, Oliver Pogarell, Felix Segmiller -- Standard EEG in Personality and Anxiety Disorders / Nash Boutros -- EEG in Delirium and Dementia / Sophia Wang, Silvana Riggio -- Effects of Psychotropic Drugs on EEG / Silvana Galderisi, Armida Mucci -- Certification and Training in EEG and Clinical Neurophysiology / Nash Boutros, Silvana Galderisi -- Index.
Includes bibliographical references and index.
Keywords: Electroencephalography; Psychiatry; Mental illness -- Diagnosis; Electroencephalography -- methods; Electroencephalography -- psychology; Mental Disorders -- diagnosis; Psychiatry; MEDICAL -- Psychiatry -- General; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Electroencephalography; Mental illness -- Diagnosis; Psychiatry; Electronic books